Synthesis, cytotoxicity and antineoplastic activities of novel acridine-based platinum(II) organometallic complexes - Ismail, Nur Amajeida; Salman, Abbas Abdulameer; Mohd Yusof, Mohd Sukeri; Che Soh, Siti Kamilah; Kadir Pahirulzaman, Khomaizon Abdul; Ali, Hapipah Mohd; Sarip, Rozie (Elsevier, 2019)
Two new platinum(II) complexes incorporating acridine ligands with aniline moieties were successfully synthesised and characterised. The acridine-based ligands were synthesised by means of Ullmann's condensation. The reaction of cis-[PtCl2(DMSO)2] with the aforementioned ligand in a specified mol ratio gives 9-phenylaminoacridine cis-dichloro(dimethylsulfoxide)-platinum(II), 2a, and bis-[N-(3,5-dimethoxyphenyl) acridin-9-amine)]chloro platinum(II), 2b. Apparently, both complexes were slightly planar and in discrete asymmetrical units. Cytotoxicity and antineoplastic activity evaluations were conducted using WRL-68, MCF-7, HT-29, and HL60 cell lines. The novel complexes exhibited potent activity towards the cell lines. Concurrently, the MTT cytotoxicity assay revealed that all complexes significantly inhibited the proliferation of MCF-7 and HL60 cells. © 2019 Elsevier B.V.